DEVELOPMENT OF VIDEO-BASED DIGITAL CONTENT LEARNING FOR TEACHING UNIVERSITY STUDENTS - Arochman, Taufik; Imron, Ali; Hantari, Winda Candra (English Review: Journal of English Education, 2024)
Nowadays, technological developments are really very fast so it requires students to be able to follow them. Like what was done during a pandemic, learning was done online so lecturers had to prepare the material properly by using internet facilities for teaching. Unfortunately, learning is still considered to have many problems during the pandemic, both in terms of material and media used, resulting in a learning loss. This study highlights the development of video-based digital content learning which are integrated into learning. The method used in this study was research and development. The steps to develop the media were applied Four-D model by Thiagarajan and Semmel. The video-based digital content learning presents interactive learning in the form of videos integrated with learning management system, ELITA. The media has been tested on 25 students at Universitas Tidar during the covid-19 pandemic and showed good acceptance. The results of this study indicate that video-based digital content is feasible and effective to be used in supporting student motivation and learning outcomes. This implies that digital content learning is of value to be used and applied in online learning for teaching university students.